Characteristics, clinical and laboratory data and outcomes of pregnant women with confirmed SARS-CoV-2 infection admitted to Al-Zahra tertiary referral maternity center in Iran: a case series of 24 patients - Maryam Vaezi; Mojgan Mirghafourvand; Shahla Hemmatzadeh (BMC, 2021)
Abstract Background Physiological changes during pregnancy put pregnant women at higher risk for COVID-19 complications. The objective of this study was to evaluate clinical and laboratory characteristics and outcomes of 24 COVID-19 pregnant patients and their newborns referred to the Al-Zahra tertiary maternity hospital in Tabriz, Iran. Methods Clinical records of 24 COVID-19 confirmed pregnant patients were retrospectively reviewed from10 March 2020 to 15 April 2020. Vertical transition was assessed through neonatal pharyngeal swab samples. The study has been approved by the Tabriz University Medical Ethics Committee (IR.TBZMED.REC.1399.497). Results There were 24 hospitalized cases with clinical symptoms and confirmed diagnosis of COVID-19. The mean age of cases was 26.5 years; most were nulliparous (54.2%), in their third trimester (62.5%) and were in the type A blood group. Clinical symptoms in order of prevalence were cough, fever, dyspnea, myalgia, anosmia, and diarrhea. Oxygen saturation (SpO2) in 70.8% cases was in the normal range (greater than 93%). The risk of premature labor or abortion in cases showed no increase. 12 cases were in ongoing normal status; on follow up, 11 cases had delivered their babies at term and one had ended in IUFD because of pregnancy-induced hypertension. All delivered babies were healthy. Caesarean section in all cases was performed under obstetric indications or maternal demand, and no relation was found between COVID-19 and Caesarean delivery. Neonatal outcomes according to gestational age in 8 cases out of 11 (72.72%) were desirable; neonatal morbidity and mortality resulted from pregnancy complications. Blood pH in 6 neonates was assessed due to immaturity and NICU admission, all of which were in normal ranges except one case related to HELLP syndrome. There was no evidence of vertical transmission. Conclusions Findings suggest that clinical symptoms in pregnancy were similar to non-pregnant women, no rise in risk of premature labor or abortion was seen, and vertical transmission was not observed in none of cases. Lymphopenia was the leading laboratory change. Given asymptomatic cases despite severe forms of infection in pregnancies, we propose screening in all suspected cases. All placentas and newborns should be tested in the field for vertical transmission.